Friction, wear and tribofilm formation with a [NTf2] anion-based ionic liquid as neat lubricant. (November 2016) - Hernández Battez, A.; Blanco, D.; Fernández-González, A.; Mallada, M.T.; González, R.; Viesca, J.L.
Abstract: This paper presents the tribological behavior of methyltrioctylammonium bis(trifluoromethylsulfonyl)imide [N1888 ][NTf2 ] ionic liquid as neat lubricant in a steel-steel contact. A ball-on-disk reciprocating rig was used: firstly, at constant frequency (15 Hz) under both variable loads (40–120 N) and sliding distances (216, 324 and 432 m); and secondly, at different frequencies (10–30 Hz) and constant both load (80 N) and sliding distance (432 m). Slight friction variations and increasing wear with rising loads was found at constant frequency. Different behavior was found at constant load. The tribofilm thickness formed on the worn surface was closely related to testing conditions and controlled tribological behavior. Highlights: Friction and wear reduction is related to tribofilm formation and thickness. Tribofilm thickness increases with load and testing time. At fixed load tribofilm thickness depend on frequency or speed.